Ciclagem de nutrientes por plantas de cobertura em pré-safra e cultivo de soja no ecótono cerradoamazônia, Mato Grosso - Tavanti, Tauan Rimoldi (2018)
In order for the soybean production system to be improved, it is necessary to study the grain production chain, thus proposing new forms and management strategies that will benefit the crop. The main objective of this study was to evaluate the productive potential and nutritional aspects of the soybean cultivated in succession to different coverage plants. Also, to verify the best option among the plants to be cultivated in pre-cropping, in front of the release of the nutrients by the time of decomposition of the straw. The dissertation is arranged in chapters, composing in addition to the general considerations presented in chapter 1, chapter 2, in which the main purpose is met. The study was conducted at the experimental station of the Federal University of Mato Grosso (UFMT), Sinop campus, in a Red-Yellow Latosol. A randomized complete block design was used in the arrangement of subdivided plots with four replicates, the main factor being the cover plants: Crotalaria spectabilis (Crotalária), Fagopyrum esculentum (Trigo Mourisco), Mucuna aterrima (Mucuna Preta), Urochloa brizantha cv. Piatã (Piatã), Urochloa ruziziensis (Ruziziensis), Eleusine coracana (Pé-de-galinha) and Pennisetum glaucum (Milheto), and the secondary factor in the sub-plots at the evaluation periods, 0, 15, 30, 45, 60, 90, 120, 150 and 180 days after desiccation (DAD). The results indicate that sowing of Piatã in pre- cropping provides greater accumulations of N, P, K, Mg, Cu, Mn and Zn for soybean. Mucuna Preta and Crotalária provided the highest leaf accumulation of Ca. Piatã promotes greater production of dry phytomass, however, Ruziziensis stands out by providing greater soil cover for a longer period of time. The half-life of the straw does not exceed 50 days, considering all the treatments proposed. The highest soybean yield was obtained with the use of Piatã in pre-cropping.